POPULASI Paradisaea minor jobiensis, Rothschild 1897 DI BARAWAI YAPEN PAPUA - Edoward Krisson Raunsay; Dorthea Fortunella Abidondifu (BERITA BIOLOGI, 2022)
The Paradisaea minor jobiensis, Rothcshild 1897 is one of the most beautiful Cenderawasih birds in Papua, especially in the Yapen Islands and is a species currently threatened with extinction. The purpose of this study is to find out the population of P. m. jobiensis in the forest area of Imbowiari Barawai. Observation of population P. m. jobiensis is done with Demographic Parameters through direct observation using IPA method and then analyzed quantitatively parametrically to see population size, density and sex ratio. The population of Cenderawasih bird in the forest area of Imbowiari Barawai is 188 individuals, of which males are 136 individuals and females are 82 individuals. The population of Cenderawasih Birds in the Imbowiari forest is still very abundant, where the males are moro dominant than females.